2002
DOI: 10.1002/jez.10013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasma from bivalve mollusk species on the in vitro proliferation of the protistan parasite Perkinsus marinus

Abstract: The in vitro culture of the Eastern oyster parasite Perkinsus marinus has provided a unique opportunity to examine its susceptibility to putative recognition and effector defense mechanisms operative in refractory bivalve species. In this study, we report the effect of supplementing the culture medium with plasma from: (1) uninfected to heavily infected Eastern oysters; (2) oyster species considered to be disease-resistant; and (3) bivalve mollusk species that are naturally exposed to the parasite but show no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…The authors stated that anti-P. marinus activity of mussel sera may depend on cytotoxic molecules other than, or in addition to, lysozyme or antimicrobial peptides. Gauthier and Vasta (2002) also showed that plasma from bivalves that are less susceptible to P. marinus infections, Mercenaria mercenaria, Anadara ovalis and, especially, M. edulis, inhibited P. marinus in vitro proliferation more effectively than that of C. virginica.…”
Section: Host-parasite Interactions: Progression Of Infection and Immmentioning
confidence: 94%
“…The authors stated that anti-P. marinus activity of mussel sera may depend on cytotoxic molecules other than, or in addition to, lysozyme or antimicrobial peptides. Gauthier and Vasta (2002) also showed that plasma from bivalves that are less susceptible to P. marinus infections, Mercenaria mercenaria, Anadara ovalis and, especially, M. edulis, inhibited P. marinus in vitro proliferation more effectively than that of C. virginica.…”
Section: Host-parasite Interactions: Progression Of Infection and Immmentioning
confidence: 94%
“…Compared with growth in unsupplemented ODRP-3, P. marinus cells grown in the presence of plasma supplements from Crassostrea gigas, Crassostrea ariakensis, or infected C. virginica oysters show reduced in vitro proliferation (20). Uninfected C. virginica plasma supplementation, however, results in only minimal inhibition of proliferation (20,29). Oyster tissue homogenatesupplemented medium produces marked changes in cell proliferation, morphology, and differentiation, including enlargement of trophozoites and induction of tomont stages, which are rarely seen in unsupplemented ODRP-3 medium but are commonly observed during infection (29).…”
mentioning
confidence: 99%
“…In an effort to more closely simulate, in vitro, the milieu to which P. marinus is exposed in vivo, oyster tissue homogenate and plasma from P. marinus-susceptible and -tolerant oyster species have been employed as culture supplements (20,21,29). Compared with growth in unsupplemented ODRP-3, P. marinus cells grown in the presence of plasma supplements from Crassostrea gigas, Crassostrea ariakensis, or infected C. virginica oysters show reduced in vitro proliferation (20). Uninfected C. virginica plasma supplementation, however, results in only minimal inhibition of proliferation (20,29).…”
mentioning
confidence: 99%
“…Gauthier et al (1995) also found that adding plasma to the commercial medium DME/Ham's F12 with low FBS concentrations (0% and 0.1%) enhanced the parasite proliferation as measured by changes of optical density. Adding plasma to DME/Ham's F12 with higher FBS concentrations (1-20%), however, greatly reduced P. marinus proliferation (Gauthier and Vasta 2002;Gauthier et al 1995) compared with medium with FBS. Results from these past studies on the full effects of plasma are however difficult to interpret because the concentrations of basal medium constituents were not held constant as the concentrations of plasma or FBS were tested.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Giardia duodenalis, an intestinal protistan of vertebrates is cultured in medium supplemented with bile (Binz et al 1992), and Trypanoplasma borreli, a pathogenic flagellate from the blood of cyprinid fishes, only grows in media containing carp serum (Steinhagen et al 2000). In the case of the genus Perkinsus, the effect of host components (i.e., plasma and tissue lysates) on in vitro proliferation has only been reported for P. marinus (Gauthier and Vasta 2002;MacIntyre et al 2003;Earnhart et al 2004). In contrast to our results with P. mediterraneus, MacIntyre et al (2003 ) found that P. marinus cultured in the chemically defined medium JL-ODRP-3 (La Peyre and Faisal 1997) supplemented with eastern oyster (C. virginica) tissue lysates had lower densities than cultures in unsupplemented JL-ODRP-3, and densities were dependent on tissue lysate concentrations.…”
Section: Discussionmentioning
confidence: 96%